Effect of oleaster (Elaeagnus angustifolia L.) flour addition combined with high‐pressure homogenization on the acidification kinetics, physicochemical, functional, and rheological properties of kefir - Gül, Latife Betül; Bekbay, Saya; Akgün, Abdullah; Gül, Osman (Wiley, 2023)
AbstractIn this study, the effects of peeled oleaster flour (OF) addition (0.5% and 1%) with high‐pressure homogenization (HPH) at 100 MPa on acidification kinetics, physicochemical, functional, and rheological properties of kefir made from bovine whole milk were investigated. The fermentation kinetic parameters such as Vmax and Tf decreased by 23.63% and 20%, respectively, with 1% OF and application of HPH. The combined use of two treatments had a positive effect on Lactobacillus and Lactococcus counts, reaching a maximum of 9.63 and 9.31 log cfu/mL, respectively. Also, total phenolic contents and antioxidant activity reached maximum values of 85.31 mg GAE/g and 17.22%, respectively. The ΔE value was more limited with HPH. The maximum firmness and water‐holding capacity values were determined in the sample produced with 1% OF and application of HPH. Rheological analysis revealed that all kefirs exhibited shear thinning behavior, and the Ostwald–de‐Waele (R2 > .99) model was suitable to describe the rheological behavior of all kefir samples. The highest viscosity (0.049 Pa.s, at 50/s shear rate) and consistency index (1.115 Pa.sn) were observed in kefir with 1% OF and application of HPH. Kefir samples were characterized as weak gel behavior because storage modulus (G') was much greater than loss modulus (G") and the power‐law model was used to characterize the viscoelasticity. The overall quality assessment indicated that the improvement of the fermentation process and the enhancement of textural and functional properties of kefir samples could be achieved with the addition of 1% OF and application of HPH.
Keywords: Functional Foods; Dietary Fiber; Skim Milk; Buffalo Milk; High-Pressure Homogenization; Performance; Fortification; Sensory Properties; Structure; Original Articles; Yogurt; Suitability; Orange Fiber; Kefir; Texture; Oleaster Flour; Rheology; 2. Zero hunger